If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3x-4=4-(-5x+6)
We move all terms to the left:
3x-4-(4-(-5x+6))=0
We calculate terms in parentheses: -(4-(-5x+6)), so:We get rid of parentheses
4-(-5x+6)
determiningTheFunctionDomain -(-5x+6)+4
We get rid of parentheses
5x-6+4
We add all the numbers together, and all the variables
5x-2
Back to the equation:
-(5x-2)
3x-5x+2-4=0
We add all the numbers together, and all the variables
-2x-2=0
We move all terms containing x to the left, all other terms to the right
-2x=2
x=2/-2
x=-1
| y4-10=-14 | | 21/4m+6=7 | | .5(2p–3)–3(3p–7)=5 | | -9=x/9-2 | | 7y+6+50+14y=180 | | 3p=7p–16 | | 3x/7=12/7 | | 15/7=-x | | 3p=7p–16 | | 3x+6=2x+5x-10 | | 4(y/3)=3(2/4) | | 2x+7+6x=-9 | | .b÷12=5;b=60 | | 2v+6=17 | | 30+x=18- | | 6q-4=5 | | 5x-12+11=8 | | 35x+5=100 | | 22+12k=-14 | | x^2+6x+0.5=0 | | 4x+10+11=20 | | 5u+7+11=12 | | 3x+4x(2x)=5x | | 16=7u-12 | | 4{,}5+1{,}5k=18-3k | | 2x+-3x=-8 | | 0.02-0.05x=-0.68+0.3x | | -11y+18=-2y+18-9y | | 4x+10×11=20 | | 3n—3=6 | | 1/2*g=3/8 | | 2.9+0.4x=1.15 |